Sustainability of insect-based feed and consumer willingness to pay for novel food: A stated preference study - Rosalba Roccatello; Simone Cerroni; Sihem Dabbou (Future Foods, 2024)
In recent years, numerous studies have highlighted insects as a promising protein source for poultry feed, offering environmental benefits and improved animal welfare. However, insects are still considered unconventional in Western diets, limiting their acceptance among consumers. This study examines to what extent information on animal welfare and environmental benefits of insect-based feed can counteract factors like neophobia and established food habits, hence enhancing consumer acceptability of novel poultry products from animals fed with insect-based feed. A contingent valuation survey involving 512 Italian consumers divided into four groups was conducted: a control group with no information, an animal welfare information group, an environmental information group, and a group receiving both sets of information. Results indicate that providing information about the advantages of insect-based feed can reduce consumer reluctance towards the innovative product. Moreover, information on environmental benefits affects consumer preferences more than information on animal welfare.